Membangun Minat Generasi Z Terhadap Investasi Reksa Dana di Jawa Barat: - - Triana, Betha; Octaviani, Haniifah; Saepudin, Lisnawati; Suryana Rachman, Cinta Chantika; Suherman, Ujang (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2024)
Building Generation Z's interest in mutual fund investing is important to educate them about the importance of investing and help them prepare for their financial future. This research aims to identify variables that can influence Generation Z's interest in investing, such as knowledge about investment, financial literacy, risk perception, motivation, promotion, and other factors. This research uses a descriptive qualitative method with a literature study approach. The results of this research show that knowledge, risk, promotion of financial literacy, motivation and perception have a positive influence and convenience has a significant influence on generation Z's interest in investing in mutual funds.